2022
DOI: 10.1038/s41598-022-09598-8
|View full text |Cite
|
Sign up to set email alerts
|

Convergence of virulence and resistance in international clones of WHO critical priority enterobacterales isolated from Marine Bivalves

Abstract: The global spread of critical-priority antimicrobial-resistant Enterobacterales by food is a public health problem. Wild-caught seafood are broadly consumed worldwide, but exposure to land-based pollution can favor their contamination by clinically relevant antimicrobial-resistant bacteria. As part of the Grand Challenges Explorations: New Approaches to Characterize the Global Burden of Antimicrobial Resistance Program, we performed genomic surveillance and cell culture-based virulence investigation of WHO cri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 70 publications
2
12
0
Order By: Relevance
“…pneumoniae isolated from marine bivalves in Brazil, consistent with our results for K. pneumoniae (Bueris et al, 2022;Citterio et al, 2020).…”
Section: Discussionsupporting
confidence: 91%
“…pneumoniae isolated from marine bivalves in Brazil, consistent with our results for K. pneumoniae (Bueris et al, 2022;Citterio et al, 2020).…”
Section: Discussionsupporting
confidence: 91%
“…Furthermore, in countries such as Canada, the USA, Korea, Kuwait, Lebanon, France, Switzerland, Portugal, Spain, Germany, Bangladesh, China, and Japan, many lineages (e.g., ST131) circulate with quite similar resistance patterns [8] (Table 2). Globally, the predominant ExPEC clone is ST131, which is clustered into clades and subclades [15,37,39,[45][46][47]. It possesses a wide variety of beta-lactamases, with the most frequent including ESBLs (bla CTX-M-14,15,27 ), AmpCs (bla FOX−5 , bla DHA-1 ), MBLs, and carbapenemases (bla NDM-1,5; bla VIM-1 , bla KPC-2,-3,-18; bla OXA-48,-181,-232 ).…”
Section: Discussionmentioning
confidence: 99%
“…The vast majority of strains in this clone are resistant to several antibiotic groups, namely beta-lactams, aminoglycosides, tetracycline, fluoroquinolones, sulfonamides, chloramphenicol and nitrofurantoin [43,44]. Moreover, in the last 15 years, this clone became the predominant high-risk international clone among ExPEC clinical isolates, as 133 of 169 collected studies have reported its presence from various clinical samples between 1995 and 2018 [15,37,39,[45][46][47].…”
Section: Cc/st131 the Worldwide Predominant High-risk Clonementioning
confidence: 99%
See 2 more Smart Citations